2021
DOI: 10.1155/2021/3337514
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Low Molecular Heparin on Preeclampsia by Inhibiting Apoptosis of Trophoblasts via the p38MAPK Signaling Pathway

Abstract: Objective. To explore the efficacy of low molecular heparin on preeclampsia by inhibiting apoptosis of trophoblasts via the p38MAPK signaling pathway. Methods. A preeclampsia rat model was established, and the effects of low molecular heparin on preeclampsia via the p38MAPK signaling pathway were analyzed based on intervention of the rats with different combinations of low molecular heparin and p38MAPK signaling pathway activator. Furthermore, a hypoxia/reoxygenation model of trophoblasts in vitro was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It has been documented that women with PE have impaired uterine decidua [ 23 ]; hypoxia/reoxygenation injury promotes Cat C expression and activation of the p38MAPK/NF-κB pathway in human umbilical vein endothelial cells, but downregulation of Cat C inhibits p38MAPK/NF-κB pathway activation and increases vascular endothelial cell activity, such as enhancing endothelial cell invasion, anti-apoptosis, antioxidant capacity and angiogenic potential [ 24 ]. The p38MAPK signaling pathway regulates apoptosis and oxidative stress in endothelial cells in PE and affects the angiogenic activity of extravillous trophoblasts; hyperactivation of the p38MAPK pathway can lead to a variety of diseases, such as PE [ 9 , 10 ]. As a classical inflammatory and oxidative stress signaling pathway, the NF-κB pathway can lead to endothelial stress, uteroplacental dysfunction, and PE [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that women with PE have impaired uterine decidua [ 23 ]; hypoxia/reoxygenation injury promotes Cat C expression and activation of the p38MAPK/NF-κB pathway in human umbilical vein endothelial cells, but downregulation of Cat C inhibits p38MAPK/NF-κB pathway activation and increases vascular endothelial cell activity, such as enhancing endothelial cell invasion, anti-apoptosis, antioxidant capacity and angiogenic potential [ 24 ]. The p38MAPK signaling pathway regulates apoptosis and oxidative stress in endothelial cells in PE and affects the angiogenic activity of extravillous trophoblasts; hyperactivation of the p38MAPK pathway can lead to a variety of diseases, such as PE [ 9 , 10 ]. As a classical inflammatory and oxidative stress signaling pathway, the NF-κB pathway can lead to endothelial stress, uteroplacental dysfunction, and PE [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] LMWH relieved pre‐eclampsia by inhibiting the p38MAPK signaling pathway, inhibiting trophoblast apoptosis, and promoting proliferation and migration. [ 12 ] LMWH combined with magnesium sulfate reduced trophoblast infiltration and ameliorated maternal hemagglutination in severe pre‐eclampsia patients. [ 13 ] Interestingly, the anti‐apoptotic effect of the Heparin‐binding epidermal growth factor (HB‐EGF) is a key factor for trophoblast survival.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%